Intellectual Similarities between Iqbal and Khawaja Ghulam Farid - Javed, Tariq; Kousar, Robina (sourcecoder, 2022)
As Allama Iqbal appears to be under the influence of Sufi poets Rumi, Hafiz, Shirazi, Urfi, Firdausi and others on account of Oriental tradition, Islamic values and his own typical bend of mind, so does his thought bear a strong resemblance to Khawaja Ghulam Farid. This article explores the intellectual similarities between Iqbal and Khawaja Ghulam Farid. In this regard, not only the books have been used, but also the opinion of experts and critics have been taken into consideration. The philosophy of Self which forms the basis of Iqbal’s poetry also flows through the entire work of Ghulam Farid. Both Emphasize and urge of total awareness of one’s ego and self in their poetry with mysticism as the predominant ambience of their creative work. The relationship of the creator, the Universe and Man has also been elaborately explained by the two. Ghulam Farid reminded a believer of Pantheism as long as he lived and so did Iqbal for greater part of his life. Both have strong conviction for love and preach unity and harmony of faith and while poetry of Iqbal imparts the message of oneness to the rejection of distinctions of race and color, so does Ghulam Farid say! “The fruit is ripened mate! Let’s pick it together. Their poetry also carries a dominant streak of austerity of living and asceticism. In this research, mix methodology will be used. Both are true devotees of the prophet (S.A.W) and to them the well. Being of entire human race lies in following his from South Punjab, Ghulam Farid, in countless ways be it longing, seeking, parting and unison or sociology, ethics, brotherhood, compassion, culture, etiquette and human greatness. Research has come to the conclusion that Iqbal and Khawaja Ghulam Farid have a lot of intellectual similarities.